PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP KEPEMIMPINAN CALON PRESIDEN REPUBLIK INDONESIA PERIODE 2019-2024 - Toedien, Fahmi Amri; Erlinda, Sri; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Public perception is very important in the sustainability of a leadership, so that leaders can assess what must be done in carrying out their leadership. Students referred to as intellectuals are considered critical of the political conditions in Indonesia, of course, having a deep perception of the two pairs of presidential candidates at this time, bearing in mind that both pairs of candidates have different character and background that will hold the highest authority in the country. This research is structured with the formulation of the problem "What is the perception of the University of Riau students towards the leadership of the presidential candidate for the republic of Indonesia in 2019-2024?" This study aims to determine the perception of Riau University students towards the leadership of the Republic of Indonesia presidential candidates in the 2019-2024 period. sampling from the whole population was taken using purposive sampling technique. The population in this study was 31,478 people. The sample in this study was taken by purposive sampling technique with a total of 150 people from all students. Data in this study were collected through observation, questionnaires, interviews, and documentation, then the data obtained were analyzed by quantitative descriptive techniques or a combination method (mix methoad). This method is done by collecting data and analyzing qualitative descriptive data at a later stage in order to strengthen the results of the research conducted. The results showed that the perception of students of the University of Riau on the leadership of the Republic of Indonesia presidential candidates in the 2019-2024 period for presidential candidates number 01 was at the "Good Enough" level, while the number of presidential candidates at 02 was at the "Good" level.Key Words: Perception, Students, Leadership.